Effect Of Yogurth Adduction In Blood Pressure Degression On Pregnant Woman With Hypertension - Nita Evrianasari; Ike Ate Yuviska; Suprihatini Suprihatini (Jurnal Kebidanan dan Kesehatan Tradisional, 2019)
The immediate factor causing high maternal mortality rate was bleeding (30,3%), especially post partum bleeding. In addition, hypertension (27.1%), infection (7.3%), and long handled parturition (1.7%) and based on pre-survey data on 27-4-2018 at public health working regency of Pesawaran occurring 2 people death due to eclampsia. This study aims to determine the effect of giving yogurt to pregnant women with hypertension in the Area of Health Service District Pesawaran Year 2018. This type of research is quantitative by using the experimental approach (pre experiment) with pretest-posttest approach with control group. The population in this study were all pregnant women with hypertension. Data in this research taken by simple purposive sample with primary data and data analysis using pretest dependent.. The results of this study showed that there was an effect of yogurt on blood pressure reduction, which mean score of sitole blood pressure before yogurt adduction was significantly higher than after yogurt adduction (p value 0,000 <0.005) and the effect of yogurt on blood pressure diastole, where scores on average diastolic blood pressure measurements before yogurt adduction were significantly higher than after adduction of yogurt. There was a significant difference in mean systole and diastole blood pressure in mothers given yogurt than not given yogurt. Hopefully, from this research should be advised so that could prevent the occurrence of pre eclampsia for pregnant women.